Analisis Semiotik Komodifikasi Kemiskinan Dalam Reality Show “Uang Kaget” Episode 482 Di GTV - Bayu Satyayoga Purwidyasmara; Widhihatmini Widhihatmini (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
This research is motivated by a reality show with the theme of poverty containing commodification practices that manipulate the show into a form of commodity that is consumed by its viewers. This practice turns poverty into a commodity that is exploited for the benefit of the media industry. This study aims to analyze the commodification of poverty in the reality show “Uang Kaget” episode 482. This study uses a qualitative approach, data was collected through observation and documentation, and it was analyzed using Charles Sanders Peirce's semiotics. The research results show that there is a commodification of poverty content in the visualization of the condition of food, clothing, housing, health, and education in the reality show "Uang Kaget" episode 482. The elements of poverty dominate in each segment of the show by displaying reality in a manipulative way so that it looks close to the real reality. The results of this study are expected to contribute to policy makers regarding reality show content, television show production creators to provide more educational, entertaining, and creative information; television program managers as reference for media policy makers; viewers to participate in supervising shows containing commodification: and the public to be more selective in appreciating television shows.